Obesity in school children as the health risk factor - Vlajković, Vladan (PONS - medicinski časopis, 2015)
ABSTRACT Objective. The study aimed to determine whether there is damage to the health of school-age children and adolescents with increased body mass and which are of different ages. Methods. The cross-sectional study included children who were divided into three school groups: grades I-IV and V-VIII and secondary school. Physical examination of study parameters included non-invasive measurement and blood samples which were taken for laboratory analysis. Body mass index (BMI), blood pressure, percentage of body fat (Deurenberg’s equation), cholesterol and triglycerides were recorded. Data were analyzed using descriptive statistics and hypothesis testing, with p£0.05. Results. There were 10 boys and 30 girls, aged 13.1±2.8 years (mean, SD), systolic blood pressure 118.8±14.1 mmHg and diastolic blood pressure 78.5±5.5 mmHg, serum cholesterol 4.48±0.72 mmol/L and triglycerides 1.26±0.71 mmol/L, and body mass index-BMI 30.72±4.68 kg/m2. Normal weight had 4 (10%) children, overweight were 14 (35%), obese grade I were 13 (32.5%), obese grade II were 7 (17.5%), obesity grade III were 2 (5%) and average body fat was 38.0±6.1%. BMI was significantly higher in children of school age and high school than children in lower grades (p=0.006) and significantly correlated with age, systolic and diastolic blood pressure and blood triglyceride levels (p<0.05). Conclusion. Current status of child nutrition included in the study represent a significant risk of disease developments, such as cardiovascular (e.g. hypertension) and metabolic illnesses (e.g. metabolic syndrome). Key words: obesity; body mass index; child; adolescent; blood pressure.